Avaliação cefalométrica do efeito do tratamento da má oclusão Classe II, divisão 1, com o bionator de Balters: estudo com implantes metálicos - Melo, Ana Cláudia Moreira (2006)
AIM: to evaluate the bionator treatment effect on Class II, division 1, malocclusion, presenting mandibular retrusion or mandibular length deficiency. METHODS: it is described the effects of the treatment in three patients that were accompanied with no treatment for one year and them were treated for two years with bionator. In all three patients metallic implants were inserted to serve as reference to cephalometric tracing superimposition that, together with some traditional cephalometric measurements, generated data to the evaluation of the orthopedic and orthodontic effects of Class II malocclusion treatment with this appliance. RESULTS AND CONCLUSIONS: it was observed a maxillary growth restriction and a stimulus of mandibular growth as well as a change in the direction of condylar growth. There was also an uprighting of the upper incisors and in the lower arch Balters bionator increased the natural tendency of buccal movement of the incisors.